2016
DOI: 10.1038/eye.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

Predicting macular hole closure with ocriplasmin based on spectral domain optical coherence tomography

Abstract: Purpose To assess the preoperative features of patients with idiopathic macular hole (IMH) and vitreomacular adhesion (VMA) treated with ocriplasmin (OCP) that can predict successful closure. Method Data were prospectively collected on all patients with IMH treated with OCP in three British ophthalmic centres. Several preoperative variables were recorded including the IMH base diameter (BD), minimum linear diameter (MLD), and VMA width measured on spectral domain optical coherence tomography. Several other IMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Steel et al. () reported that FTMH in a presumably earlier stage with narrow MLD relative to BD, had a greater chance to close following intravitreal ocriplasmin injection. These observations allow us to propose a model of FTMH maturation from a cylinder shape into an hourglass shape, which is accelerated by the release of the VMT.…”
Section: Discussionmentioning
confidence: 99%
“…Steel et al. () reported that FTMH in a presumably earlier stage with narrow MLD relative to BD, had a greater chance to close following intravitreal ocriplasmin injection. These observations allow us to propose a model of FTMH maturation from a cylinder shape into an hourglass shape, which is accelerated by the release of the VMT.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, treatment of early FTMH with intravitreal gas injection seems discouraging in our study. Steel et al [22] recently showed that MHs with a narrower base configuration relative to the minimum linear diameter had a higher closure rate when treated with ocriplasmin. Due to the small number of cases, we could not verify the relationship between the MH configuration and success rate in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…To better identify OCT features that may predict hole closure other than hole size, Steel et al prospectively evaluated outcomes in 31 eyes with idiopathic small or medium FTMH treated with ocriplasmin [18]. Mean hole size was 278 μm (range 80–395 μm).…”
Section: ‘Real-world’ Clinical Outcomes and Patient Selectionmentioning
confidence: 99%